Penjatuhan Pidana di Bawah Ancaman Pidana Minimum dalam Putusan Mahkamah Agung Nomor 1278 K/Pid.Sus/2022 Ditinjau dari Prinsip Keadilan - I Made Rudy Darmika (Jurnal Yusthima, 2026)
Drug-related offenses constitute serious crimes addressed through strict penal policies, one of which is the establishment of special minimum penalties under Law Number 35 of 2009 on Narcotics. However, in judicial practice, the application of such minimum penalties is not always implemented rigidly, as reflected in Supreme Court Decision Number 1278 K/Pid.Sus/2022, which imposed a sentence below the statutory minimum on a narcotics user possessing a very small quantity of evidence. This study aims to analyze the application of the principle of justice in the imposition of sentences below the statutory minimum and to examine the legal rationality underlying such a decision within the framework of the Indonesian sentencing system. This research employs a normative legal research method using statutory, historical, and conceptual approaches, through an examination of relevant legislation, criminal law doctrines, and court decisions. The findings indicate that the imposition of a sentence below the statutory minimum in this decision reflects an effort to realize substantive justice through the application of the principles of proportionality and individualized sentencing. The decision demonstrates that justice is not always synonymous with the mechanical application of the law, but rather requires an interpretation that takes into account the concrete circumstances of the case, the degree of the offender’s culpability, and the objectives of punishment. Accordingly, this study underscores the importance of balancing legal certainty and substantive justice to ensure that the sentencing system remains grounded in humanitarian values without undermining legal legitimacy.